1987
DOI: 10.1007/bf02370706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trickle fertigation with three forms of nitrogen on soil pH, levels of extractable nutrients below the emitter and plant growth

Abstract: The effects of application of nitrogen as calcium nitrate, urea or ammonium sulphate at two rates through the trickle irrigation system on pH and nutrient status of the wetted volume of soil below the emitters and on growth and nutrition of courgette (zucchini) plants (Cucurbita pepo L.) was investigated.Soil acidification, caused by nitrification, occurred to a large extent in the volume of soil immediately below the emitters in the urea and ammonium sulphate treatments. Acidification was greater at the high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
5

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 19 publications
(17 reference statements)
1
22
0
5
Order By: Relevance
“…O mesmo comportamento pode ser observado para os valores de Mg. Segundo Haynes & Swift (1987), a acidificação do solo na região atingida pela irrigação resulta em significativa redução nos teores de Ca, Mg e K extraídos na análise do solo amostrado nestes locais. O comportamento do íon K observado no presente experimento não segue o padrão estabelecido por estes autores.…”
Section: Análise Química De Solounclassified
“…O mesmo comportamento pode ser observado para os valores de Mg. Segundo Haynes & Swift (1987), a acidificação do solo na região atingida pela irrigação resulta em significativa redução nos teores de Ca, Mg e K extraídos na análise do solo amostrado nestes locais. O comportamento do íon K observado no presente experimento não segue o padrão estabelecido por estes autores.…”
Section: Análise Química De Solounclassified
“…Uma forma de contornar esse problema é o uso de uma fonte amoniacal conjugada com uma fonte nítrica. Haynes & Swift (1987) estudaram o efeito da aplicação de nitrato de cálcio, sulfato de amônio e ureia em duas doses, por meio de sistemas irrigados por gotejamento sobre o crescimento e a produção do mamoeiro. Os autores verificaram aumento no crescimento e na produção do mamoeiro com a aplicação de nitrogênio.…”
Section: Introductionunclassified
“…Edwards et al, (1982) observed that application of NH 4 NO 3 through drip irrigation system decreased the soil pH in the top 30cm. Haynes and swift (1987) concluded that with increasing soil acidification, the leaching of cations viz., Ca 2+, Mg 2+ , K + and Na were also in greater amounts. Soil acidification appeared to inhibit nitrification as levels of NO 3 clearly decline below pH 5.5 and at the same time levels of NH 4+ increased greatly.…”
Section: Effect Of Fertigation On Soil Chemical Propertiesmentioning
confidence: 99%
“…Soil acidification caused by nitrification, occurred to a large extent in the volume of soil immediately below the emitters when fertigated with urea and ammonium sulphate (Haynes and Swift, 1987).…”
Section: Effect Of Fertigation On Soil Chemical Propertiesmentioning
confidence: 99%